HUBUNGAN ANTARA KOEFISIEN EFEK SPURIOUS OVERLAP (ESO) DENGAN INDEKS RELIABILITAS ITEM (iri) TES KEMAMPUAN BERPIKIR MANTIK - I Gusti Ngurah Puger; I Nyoman Suprapta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to determine the significant relationship between the spurious overlap effect (ESO) coefficient and the item reliability index (IRI) of the logical thinking ability test. This research is a correlational study. Correlational research is a type of research that aims to find the relationship between one variable and another. The population of this study was all eighth-grade students of SMP Negeri 2 Seririt, while the sample consisted of the responses of 100 eighth-grade students of SMP Negeri 2 Seririt after being administered a logical thinking ability test, selected using purposive sampling. Purposive sampling is a sampling method in accordance with the previously established research objectives. The instrument needed to obtain data in the form of test responses was a logical thinking ability test. The logical thinking ability test used was deemed suitable for further use, as assessed by the content validity coefficient (VI), the inter-rater response reliability coefficient (rxx'), item validity, and test reliability (rxx'). To analyze the data regarding the relationship between the spurious overlap effect coefficient and the item reliability index (IRI) of the logical thinking ability test, the Pearson Product Moment correlation formula was used. The data analysis revealed that the spurious overlap effect (ESO) coefficient was inversely related to the item reliability index (IRI) of the logical thinking ability test. Based on the findings presented, it can be concluded that the spurious overlap effect (ESO) coefficient was inversely related to the item reliability index (IRI) of the logical thinking ability test.